JIGSAW PUZZLE JIGSAW PUZZLE GAME GROUP ACTIVITY THERAPY TO IMPROVE ELDERLY SOCIAL INTERACTION ABILITY IN LOK BAINTAN VILLAGE IN RT 02, BANJAR DISTRICT: TERAPI AKTIVITAS KELOMPOK JIGSAW PUZZLE GAME UNTUK MENINGKATKAN KEMAMPUAN INTERAKSI SOSIAL LANSIA DI DESA LOK BAINTAN DALAM RT 02 KABUPATEN BANJAR - Idres, Ahmad Habibi; Anggraini, Afni; Aisah, Nur; Irma Nur Aina, Siti; Tasalim, Rian; Anshor, A (Batik-MU : Jurnal Pengabdian Masyarakat, 2023)
Old age is the last stage of life that humans go through, where at this time a person experiences physical, mentally, and social decline little by little so that he cannot carry out his daily tasks anymore (declination stage). Feelings of inferiority experienced by the elderly result in the elderly feeling inferior and reduced in their social interactions. Lack of social interaction can lead to feelings of loneliness in the elderly. Loneliness is a feeling of discomfort associated with a desire to have more contact with other people. The consequences of feeling lonely can cause stress, depression, and an unstable mental status. Based on the results of a survey conducted by our group in the village of Lok Baintan Dalam RT 02, there are many elderly people who have experienced a decrease in their social interactions and most of the elderly just stay silent in their respective homes. The service activities that we do to overcome the problems of social interaction in the area are by doing jigsaw puzzle group activity therapy (GAT). Jigsaw puzzle therapy is carried out because in this game it can train cooperation, thinking skills, train coordination between the elderly, train reason, and also patience. The results of this service activity after the GAT was carried out, the ability of the elderly's social interaction increased as evidenced by the results of the social interaction questionnaire which showed the results of the social interaction of the elderly in the area in the good category